Manufacture and Characterization of Supercapacitance Properties of Robusta Coffee Shell-Based Carbon Electrodes - Frida Margareth Hulu (Talenta Publisher, 2023)
Supercapacitors, which are able to store large amounts of energy, are a major requirement in energy utilization. In this study, carbon electrodes were produced from robusta coffee shells. The carbon was activated with 0.5 M, 0.7 M, and 3 M of KOH. The results showed that the higher the concentration, the larger and more regular the pores on the carbon and the larger the size. Carbon is produced in an impure state. The specific capacitances produced with 0.5 M, 0.7 M, and 3 M KOH are 0.28 Fg-1, 0.11 Fg-1, and 0.10 Fg-1.